Performance and preliminary design of nutating disc engine topping cycles for civil aero-engine applications. - Sebastiampillai, Joshua Marius (Cranfield University, 2018)
Within the next thirty years evolutionary approaches to aero engine development will struggle to keep abreast with ever stringent environmental targets. A key component of the environmental targets stipulated by the SRIA is to reduce mission fuel burn by 75% by the year 2050, when compared to a year 2000 baseline. If the mission fuel burn benefits attributed to flight path optimization are excluded, a fuel burn target of 68% is postulated. Therefore, radical approaches to aero-engine development in terms of thermal and propulsive efficiency improvements need to be considered. One particular concept involves the inclusion of an un-ducted contra rotating propeller array to increase the propulsive efficiency of an aero-engine, for a short range aircraft, by the 2050 time frame. Concurrently a pressure-rise combustion system, called the nutating disc engine system, can increase the thermal efficiency of the year 2050 short-haul engine. The nutating disc engine system concept is a strong contender due to its power density. The feasibility of the nutating disc engine system has been previously investigated for unmanned vehicle applications. However, this work investigates the performance benefits of incorporating a nutating disc engine system in a geared open rotor engine for the year 2050. According to the investigated literature, a methodology to size the nutating disc engine system and predict its potential fuel burn performance benefit in a geared open rotor configuration is lacking. In addition, there is a lack of knowledge regarding the impact synergetic technologies such as intercooling and secondary combustion affect the performance of a nutating disc engine system coupled to an un-ducted contra rotating propeller array. Hence, the primary contribution of this work is to determine a methodology to predict the size and turbo-charged performance of a nutating disc engine system. An outcome of this contribution determines whether a geared open rotor engine with a nutating disc engine system can meet the fuel burn target of 68%, when compared to a year 2000 baseline engine. This investigation is furthered with an uncertainty analysis, to show the variability of potential 2050 fuel burn estimates. The derived nutating disc engine system sizing methodology shows confluence with known prototype dimensions and CAD based sizing approaches. The used thermodynamic model also shows reasonable levels of confluence with published literature. Another outcome of the primary contribution to knowledge, is to determine whether synergetic technologies such as intercooling and secondary combustion can meet the 68% fuel burn target in conjunction with a nutating disc engine system in a geared open rotor engine architecture. These investigations are furthered by an uncertainty analysis. The secondary contribution of this work is to provide preliminary performance and mass estimates of Y2050 engine configurations that can meet the 68% fuel burn target. An engine specification for a year 2000 baseline engine and a reference year 2050 geared open rotor engine are proposed to benchmark the relative fuel burn benefit achieved by a perceived year 2050 nutating disc engine system engine configurations. The reference 2050 geared open rotor engine, on a short range aircraft, determines engine technology levels for further radical engine configurations in this work. The reference year 2050 engine, geared open rotor, produces a fuel-burn benefit of 58.9% relative to a comparable year 2000 baseline. Since it falls short of the 68% target fuel-burn benefit, the viability of a nutating disc engine system is considered. A geared open rotor with a nutating disc engine system can provide fuel burn benefits of 63% relative to a year 2000 baseline. An uncertainty study indicates, that the proposed engine configuration can provide relative fuel burn benefits from 37% to 71%, when compared to a year 2000 baseline. The inclusion of intercooling, secondary combustion and a combination of the two with a nutating disc engine system produced fuel burn benefits of 64%, 71% and 65% respectively relative to year 2000 baseline, as a consequence of a targeted search optimization. The design variables that influence the uncertainty the most in all the investigated nutating disc engine variants are the heat flux through the casing and the ratio of constant volume combustion to constant pressure combustion. A like for like analysis, for the four investigated engine configurations indicate that a geared open rotor with only a nutating disc engine system provides the highest potential fuel burn benefit. However, when aspects such as NOx and noise emissions are considered qualitatively it is postulated that a nutating disc engine system with intercooling and secondary combustion technologies is desirable. Due to the high degree of uncertainty in the perceived fuel burn values, for the proposed engine configurations, a roadmap to progress the nutating disc engine system technology to higher TRL are further detailed.
Keywords: Nutating disc engine; geared open rotor; SRIA; intercooler; secondary combustor; pressure-rise combustion system